Analisis Forecasting penjualan pupuk urea pada PT XYZ dengan metode Single Exponential Smoothing (SES) dan Holt’s - Saifullah, Iqbal; Winursito, Yekti Condro (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
XYZ Company is a company engaged in fertilizer production in Indonesia. Fertilizer producers are faced with a number of challenges, namely demand fluctuations caused by seasonal factors or changes in consumption trends that often make fertilizer production difficult to predict. The company currently has inaccurate forecasting on fertilizer production as a result of which there is an excess or shortage of fertilizer production. This research aims to solve the problem of forecasting calculations and selecting the best forecasting method to be used in the amount of fertilizer production at XYZ Company. The methods used are the Single Exponential Smoothing method and Holt's method. Data processing will be carried out with Excel software using sales data in the previous period at XYZ Company. Based on the data processing that has been done, it can be seen that Holt's method is the best method to be used to forecast the amount of fertilizer production at XYZ Company. This is evidenced by the results of forecasting calculations and also the results of forecasting error tests that have been carried out where the Holt's method has the best results